ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM SOAL TURUNAN BERDASARKAN KELOMPOK GENDER MASCULINE - Amelia, Kadek Devy; Lefrida, Rita; Alfisyahra, Alfisyahra; Pathuddin, Pathuddin (Universitas Tadulako, 2025)
This research aims to obtain a profile of students' Mathematical Communication Skills in derivative problems. Based on the Masculine Gender Group. The research uses a descriptive qualitative approach. The subjects in the research were three people from class XI students at SMA Negeri 1 Sigi. Subject selection is based on masculine gender. Data collection techniques include written tests, interviews and discussions. The research method uses within-method triangulation. The research results showed that (1) students with masculine gender stated the information in the questions using their own language, repeated their friends' explanations, wrote down ideas for solving derivative questions and wrote down the reasons for each step in solving the questions. clear (2) students with masculine gender can read the symbols contained in the derivative questions, write limit notation, explain the meaning of the graph in the picture. This subject can also repeat the explanation of the theme. Furthermore, (3) students with masculine gender can make conclusions from solving questions.